Hubungan Sikap Kerja Duduk Dan Durasi Kerja Terhadap Keluhan Musculoskeletal Pada Pedagang - Indah Pramita; Luh Putu Ayu Vitalistyawati; Ni Putu Fortuna Masayuki (LPPM Universitas Abdurrab, 2022)
Traders at the wangaya flower market do their jobs in a static sitting posture. This attitude is carried out for 10 hours every day starting at 11.00 – 21.00 WITA. The duration of work for 10 hours is the duration of work that exceeds the normal time. When working with a static sitting posture, the back muscles will be burdened. If the attitude of this work is done continuously to the excessive duration of action, it can lead to musculoskeletal disorders. This research uses cross sectional method. The study population was 45 people with a sample of 10 people obtained based on the research criteria. This study uses the Rapid Entire Body Assessment and Nordic Body Map Questionnaire measuring instruments. Furthermore, hypothesis testing is carried out using the Sprearman's rho test. The results of the Spearman's rho test show a value of 0.664 which means the close relationship between work attitudes and work duration on musculoskeletal complaints in traders is strong.